HUBUNGAN USIA, PARITAS DAN JARAK KEHAMILAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS GANTIWARNO - Rahayu, Esti (Jurnal Kesehatan, 2022)
Anemia in pregnancy is the condition of the mother with hemoglobin levels below 11 g/dl in the 1st and 3rd trimesters or levels <10.5 g/dl in the 2nd trimester. , 06%) cases from 392 pregnant women, in 2014 as many as 17 (4.06%) cases from 418 pregnant women, in 2015 as many as 21 (6.03%) cases from 348 pregnant women, in 2016 as many as 7 (2.07 %) ) cases of 338 pregnant women. The purpose of this study was to determine the relationship between age, parity and pregnancy distance with the incidence of anemia in pregnant women in the work area of thegantiwarno health center in 2017. This type of research was analytical, the number of samples was 89 pregnant women taken by cluster sampling technique. The method of measurement used a questionnaire sheet and a digital Hb measuring instrument, analyzed univariately with presentation and bivariate with chisquare. From the results of the study, it was found that pregnant women who experienced pregnancy anemia in the work area of Puakesmas Ganwarno in 2017 were mostly aged 20-35 years, namely 71 cases (79.8%), primiparous parity as many as 50 cases (56.1%), 2 years gestation interval 77 cases (86.5%). From the results of the discussion, there is a relationship between age and the incidence of anemia in pregnant women with P-value 0.045 < (0.05), there is a relationship between parity and the incidence of anemia in pregnant women with Pvalue 0.000 < (0.05) and OR 0.156, and there is a relationship between the distance between pregnancy and the incidence of anemia in pregnant women with P-value 0.033 < (0.05) and OR 3.923. It is recommended for pregnant women to be diligent in attending maternal classes, do ANC regularly at least 4 times during pregnancy and 90 Fe tablets during pregnancy and consume foods that support anemia prevention such as meat, green vegetables and other nutritious foods, and it is also expected for husbands to remind their wives every day to take Fe tablets.